1981
DOI: 10.1017/s0022112081000414
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the end effects on the wake of a circular cylinder towed through water at low Reynolds numbers

Abstract: At low Reynolds numbers, three-dimensional features are frequently observed in the vortices shed behind a basically two-dimensional circular cylinder. This paper deals with the dependence of the configuration of the vortices on various end constructions. The cylinder is towed at a uniform speed in a water tank and simple flow visualization is used. It is found that the three-dimensional structure of the wake depends strongly on the flow configuration at each end of the cylinder. The boundary condition imposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(49 citation statements)
references
References 10 publications
5
43
0
1
Order By: Relevance
“…Dye visualization showed that with this clearance the end effects are significantly reduced and do not reach more than two chord lengths across the span. These observations are in qualitative agreement with similar experiments on cylinders by Slaouti & Gerrard (1981).…”
Section: Three-dimensional Effectssupporting
confidence: 92%
“…Dye visualization showed that with this clearance the end effects are significantly reduced and do not reach more than two chord lengths across the span. These observations are in qualitative agreement with similar experiments on cylinders by Slaouti & Gerrard (1981).…”
Section: Three-dimensional Effectssupporting
confidence: 92%
“…We can see that this amplitude is strongly diminished near the free ends of the cylinder as reported in the numerical work of Dauchy et al (1997). We also note that, from #ow visualizations, Slaouti & Gerrard (1981) state that the free-end e!ect is to suppress the vortex shedding in the vicinity of the ends.…”
Section: Periodic Regimesupporting
confidence: 76%
“…Free-end cylinder wakes have also been investigated numerically by Dauchy et al (1997) and experimentally by Slaouti & Gerrard (1981); they report that the vortex shedding is diminished or suppressed near the free ends.…”
Section: Introductionmentioning
confidence: 99%
“…This 'grazing' end condition, coupled with a clean free surface at the upper end, was recommended by Slaouti & Gerrard (1981) and Lisoski (1993) for achieving predominantly two-dimensional flow along the span of a model in a towing tank. For this experiment (plotted as a dash-dotted line in figure 2), there is instead a C D minimum centred on T = 5.…”
Section: Drag Force Measurementsmentioning
confidence: 99%